Differences In Multiple Intelligences Based On Gender - Hasanuddin, Hasanuddin (Granada El-Fath, 2024)
This research will determine whether there are differences in multiple intelligences in students based on gender. This research is a comparative quantitative study with a population of 495 students and a total sampling technique. The data analysis technique used is the independent sample t-test technique. The data analysis revealed significant differences in multiple intelligence between male and female students. The statistical value was 2.908, with a p-value of 0.004. This confirms that the hypothesis in this study was accepted, indicating that female students exhibited higher levels of multiple intelligence than male students. Male students are more dominant in logical-mathematical intelligence, intrapersonal intelligence, and bodily-kinesthetic intelligence. Female students, on the other hand, are more dominant in linguistic-verbal, visual-spatial, interpersonal, naturalistic, existential, and musical-rhythmic and harmony intelligence.